2021
DOI: 10.1038/s43247-021-00199-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA signatures distinguish between tsunami and storm deposition in overwash sand

Abstract: Sandy onshore deposits from tsunamis are difficult to distinguish from storm deposits, which makes it difficult to assess coastal hazards from the geological record. Here we analyse environmental DNA from microbial communities preserved in known tsunami and storm-deposited sediments and intercalating soils and non-marine sediments near Cuddalore, India, and Phra Thong Island, Thailand. Both sites were impacted by the 2004 Indian Ocean Tsunami and a subsequent storm flooding event (2011 Cyclone Thane at Cuddalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…While all the seawater samples we collected using Lander (Methods), those from the trench bottom still show significant differences from the sediment, further confirming the stability of our conclusions. All these results, from different aspects, indicated that the ecological niche differentiation of microbial community composition might be influenced by marine geological conditions and hydrological factors, which is related to the availability of organic matter and redox pairs, and/or stochastic processes such as currents (Chen et al, 2023 ; Jing et al, 2022 ; Yap et al, 2021 ; Zhou et al, 2022 ). The trench sediment ecosystems were reported to be dominated by stochasticity in previous study (Sun et al, 2024 ), indicating that factors such as drift and dispersal are more likely to form and exist in trenches.…”
Section: Discussionmentioning
confidence: 99%
“…While all the seawater samples we collected using Lander (Methods), those from the trench bottom still show significant differences from the sediment, further confirming the stability of our conclusions. All these results, from different aspects, indicated that the ecological niche differentiation of microbial community composition might be influenced by marine geological conditions and hydrological factors, which is related to the availability of organic matter and redox pairs, and/or stochastic processes such as currents (Chen et al, 2023 ; Jing et al, 2022 ; Yap et al, 2021 ; Zhou et al, 2022 ). The trench sediment ecosystems were reported to be dominated by stochasticity in previous study (Sun et al, 2024 ), indicating that factors such as drift and dispersal are more likely to form and exist in trenches.…”
Section: Discussionmentioning
confidence: 99%
“…Such foliation of the fine fraction is then related to specific flow conditions that have been linked to a seiche effect and thus probably an earthquake event [30,219]. Molecular techniques such as sedimentary DNA are also promising to accurately discriminate between modern tsunami and storm deposits in coastal systems [268,269].…”
Section: Other Approachesmentioning
confidence: 99%
“…A recent review by Chagué-Goff et al [78] has demonstrated that geochemical proxies when combined with a good knowledge of the geological context of the studied site and of depositional and chemical processes, can be a powerful tool to differentiate tsunami deposits. New proxies also include ancient DNA for the characterization of microbial communities or microfossil assemblages in sediments [79,80].…”
Section: Holocene Record Of Tsunamis In Greece 41 Main Geological and Geomorphological Evidencementioning
confidence: 99%